Beneficial effects on host energy metabolism of short-chain fatty acids and vitamins produced by commensal and probiotic bacteria - Leblanc, Jean Guy Joseph (2017)
The aim of this review is to summarize the effect in host energy metabolism of the production of B group vitamins and short chain fatty acids (SCFA) by commensal, food-grade and probiotic bacteria, which are also actors of the mammalian nutrition. The mechanisms of how these microbial end products, produced by these bacterial strains, act on energy metabolism will be discussed. We will show that these vitamins and SCFA producing bacteria could be used as tools to recover energy intakes by either optimizing ATP production from foods or by the fermentation of certain fibers in the gastrointestinal tract (GIT). Original data are also presented in this work where SCFA (acetate, butyrate and propionate) and B group vitamins (riboflavin, folate and thiamine) production was determined for selected probiotic bacteria.